2006
DOI: 10.1111/j.1600-0420.2006.00654.x
|View full text |Cite
|
Sign up to set email alerts
|

Deep sclerectomy for the treatment of exfoliation and primary open‐angle glaucoma

Abstract: . Purpose:  To retrospectively compare the efficacy of deep sclerectomy in the treatment of primary open‐angle glaucoma (POAG) and exfoliation glaucoma (ExG). Methods:  Deep sclerectomy with either collagen or hyaluronate implants was performed in 31 eyes (45%) with POAG and 38 eyes (55%) with ExG. Pre‐ and postoperative intraocular pressure (IOP) was recorded, as was the number of glaucoma medications used pre‐ and postoperatively in each group. The follow‐up data referred to a mean period of 18 months (rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…However, our earlier series of 69 consecutive DS surgeries in POAG and ExG showed that success rates are equally good in both glaucoma types. 28 On the basis of our results, the high-inflammatory cell count at the time of the operation is a risk factor for the surgical failure during the follow-up of 3 years. Furthermore, the statistically higher number of inflammatory cells in the conjunctiva of the failed POAG than failed ExG suggests that at least in ExG, there are additional risk factors for failing DS.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, our earlier series of 69 consecutive DS surgeries in POAG and ExG showed that success rates are equally good in both glaucoma types. 28 On the basis of our results, the high-inflammatory cell count at the time of the operation is a risk factor for the surgical failure during the follow-up of 3 years. Furthermore, the statistically higher number of inflammatory cells in the conjunctiva of the failed POAG than failed ExG suggests that at least in ExG, there are additional risk factors for failing DS.…”
Section: Discussionmentioning
confidence: 91%
“…Conjunctival biopsies were obtained during DS surgery from 11 The surgical technique has been described earlier. 28 DS surgery was classified as successful if the IOP was less than or equal to 18 mm Hg without any antiglaucoma drugs and there was no requirement for repeated surgery. Moreover, if IOPs were higher than 18 mm Hg with or without the need for initiation of medical therapy and/or for a reoperation, the surgery was considered failed.…”
Section: Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…8 In an attempt to lower the incidence of complications of trabeculectomy, nonpenetrating glaucoma surgery (NPGS) was developed. [9][10][11][12][13][14][15][16][17][18][19][20] There is increasing evidence that deep sclerectomy is probably more appropriate for uveitic glaucoma. Auer et al have reported that nonpenetrating deep sclerectomy has controlled the intraocular pressure in 90% of eyes with uveitic glaucoma that were resistant to medical therapy, with low rate of surgical complications compared to classical trabeculectomy.…”
mentioning
confidence: 99%
“…Deep sclerectomy surgery has been suggested as an alternative to trabeculectomy [9][10][11][12][13][14][15][16][17][18][19]. The nonopening of the anterior chamber and the avoidance of a peripheral iridectomy may lower the incidence of such complications while retaining the efficacy of trabeculectomy [8,[10][11][12][13][14][15][16][17][18][19][20].…”
mentioning
confidence: 99%